Влияние термической обработки на свойства деформируемых алюминиевых сплавов - Яковлев, Ф. И.; Маршуба, Вячеслав Павлович (НТУ "ХПИ", 2004)
In the article the problems, concerning to definition of the regularities for influence of heat treatment on stress-strain properties of wrought aluminum alloys, are considered. On the basis of the obtained regularities the optimum performance for hardening, which allows obtaining the maximum accessible values of stress-strain properties, is defined.
Keywords: пластичность; медь; магний; свойства механические; температура